Examining Insula–Default Mode Network Functional Connectivity and Its Relationship with Heart Rate Variability - Marlene Nogueira; Juliana da Silva Magalhães; Adriana Sampaio; Sónia Sousa; Joana F. Coutinho (Brain Sciences)
Background: The Default Mode Network (DMN) is involved in self-referential and emotional processes, while the insula integrates emotional and interoceptive signals. Functional connectivity between the insula and the DMN is proposed to enhance these processes by linking internal bodily states with self-referential thoughts and emotional regulation. Heart Rate Variability (HRV), a measure of parasympathetic regulation of cardiac activity, has been associated with the capacity to regulate autonomic arousal. This study explored the relationship between insula–DMN functional connectivity and HRV. We hypothesized that (1) insula’s functional activity and volume would be related to HRV; (2) insula activation would be functionally connected with the DMN; and (3) stronger insula–DMN connectivity would correlate with higher HRV. Methods: Forty-three healthy adults underwent a structural and functional MRI acquisition to assess insula–DMN connectivity during resting state. HRV was measured also at rest using the BIOPAC system. Results: A significant positive correlation was found between insula–DMN connectivity, but no correlation was observed between insula–DMN connectivity and HRV. We also found a positive significant association between left insula volume and HRV. Conclusions: These findings suggest that while the AI and DMN are functionally interconnected, this connectivity may not be directly related to HRV. The results highlight the complexity of the relationship between brain connectivity and autonomic function, suggesting that other factors may influence HRV.